2003
DOI: 10.1017/s0305000903005579
|View full text |Cite
|
Sign up to set email alerts
|

Phonological neighbourhoods in the developing lexicon

Abstract: Structural analyses of developing lexicons have provided evidence for both children's holistic lexical representations and sensitivity to phonetic segments. In the present investigation, neighbourhood analyses of two children's (age 3;6) expressive lexicons, maternal input, and an adult lexicon were conducted. In addition to raw counts and frequency-weighted counts, neighbourhood size was calculated as the proportion of the lexicon to which each target word is similar, to normalize for vocabulary size differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 27 publications
11
90
0
Order By: Relevance
“…She concluded that children must have considerable acoustic-phonetic skill to be able to differentiate words in their lexicons. Coady and Aslin (2003) found that phonological neighborhoods are actually denser in the developing lexicon than in the mature lexicon, relative to vocabulary size. They concluded that children are not maintaining maximal distinctiveness among their lexical entries but rather are building their lexicons with a preference for words that contain more frequent phonotactic patterns.…”
Section: Evidence Of More Fine-grained Lexical Representations In Chimentioning
confidence: 88%
See 2 more Smart Citations
“…She concluded that children must have considerable acoustic-phonetic skill to be able to differentiate words in their lexicons. Coady and Aslin (2003) found that phonological neighborhoods are actually denser in the developing lexicon than in the mature lexicon, relative to vocabulary size. They concluded that children are not maintaining maximal distinctiveness among their lexical entries but rather are building their lexicons with a preference for words that contain more frequent phonotactic patterns.…”
Section: Evidence Of More Fine-grained Lexical Representations In Chimentioning
confidence: 88%
“…Dobrich and Scarborough (1992) did indeed find some evidence of these selectional constraints, but only at the earliest stages of lexical acquisition. More recent analyses of the structure of the developing lexicon have shown that childrenÕs lexicons actually contain many similar-sounding words (Coady & Aslin, 2003). Furthermore, the neighborhood structure of childrenÕs early lexicons suggests that children might actually construct their lexicons by exploiting the more familiar and frequent sound patterns rather than by filling in the acoustic-phonetic gaps in the lexicon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that examined learning of novel word forms alone (word-form learning) as well as learning of novel word forms paired with referents (word learning), Heisler (2005) found facilitative effects of both higher phonotactic probability and higher neighbourhood density. Retrospective analyses indicate that higher neighbourhood density is associated with an earlier age of acquisition, once again suggesting that neighbourhood density facilitates word learning, at least for certain types of words (Coady & Aslin 2003;Storkel 2004). Hollich et al (2000bHollich et al ( , 2002 and Swingley & Aslin (2007) experimentally examined the effect of neighbourhood density on word learning in toddlers, finding that this variable did affect word learning, although in these studies the effect was found to be reversed, so that learning appeared to be better for word forms from low-rather than high-density neighbourhoods.…”
Section: Recent Foci Of Investigationmentioning
confidence: 93%
“…Not all the data fit this story, however. There may be as much overlap in small vocabularies as in larger ones (Coady & Aslin, 2003), and studies of infants' word processing have found evidence that their word representations have more phonetic detail than the global/wholeword account would suggest (Swingley & Aslin, 2000). It is an open question at this point just what developmental changes occur in children's phonological representations and what might cause any such changes.…”
Section: Phonological Developmentmentioning
confidence: 99%